Epistemology a contemporary introduction to the theory of knowledge - Audi, Robert 1941- (Routledge contemporary introductions to philosophy, 2002)
"Epistemology, or the theory of knowledge, is concerned with how we know what we do, what justifies us in believing what we do, and what standards of evidence we should use in seeking truths about the world and human experience. This comprehensive book introduces the concepts and theories central for understanding knowledge. This revised edition builds on the topics covered in the widely acclaimed first edition and includes new material on subjects such as virtue epistemology, social epistemology and feminist epistemology. The chapter on moral, scientific and religious knowledge has also been expanded and revised."--BOOK JACKET.